Analysis of the effectiveness of organic compounds from the amine group in precipitating ions from soda production wastewater - Janina Piekutin; Adam Gołub; Jacek Leszczyński (Water Resources and Industry)
Treating wastewater from the soda industry is a complicated and lengthy process, requiring a great deal of labor and financial resources. No method has yet been developed to eliminate the environmental damage caused by the soda industry entirely. The leakage of highly contaminated soda production wastewater into soils, groundwater, and surface water can cause corrosion of water infrastructure and deterioration of water quality for both drinking and agricultural use. Soil contamination from post-production wastewater leads to erosion and adversely affects vegetation. The work focused on the removal of chloride, sulfate, calcium, and sodium from soda production wastewater by precipitation using organic solvents such as isopropylamine (IPA), diisopropylamine (DIPA), propylamine (PA) and ethylamine (EA) in various proportions. Statistical modelling through Bayesian beta regression was used to select the amine most effectively removing the tested ions in precipitate form. The effect of precipitating agent dosage on the pH and conductivity of the solution was also investigated. Samples of wastewater obtained from the soda industry were characterized by high values of pH (up to 11.9), specific electrolytic conductivity (up to 128 mS cm−1), and high concentrations of sodium (up to 13 g L−1), chloride (up to 60 g L−1) and calcium (up to 24 g L−1) ions. Solvent-based precipitation showed that organic solvents are effective in precipitating salts from wastewater from the soda industry. Sulfate and chloride removal efficiencies of 85.1 and 34 %, respectively, were observed. Statistical analysis showed that isopropylamine was the most effective amine for ion removal.